The Association of Healthy Eating Index and Sleep Disorders: A Meta‐Analysis - Wei Guo; Yibo Dong; Yang Xu; Yan Liu; Fengdan Wang; Sizhe Wang; Zibo Wu; Yuqi Gao; Bo Li (Brain and Behavior, 2025)
ABSTRACT Background Sleep disorders are problems that include both the quality and the time of sleep. It is related to overall diet quality, and dietary patterns also affect the quantity and quality of sleep in humans. The Healthy Eating Index (HEI) is widely used to assess the quality of diet. Epidemiological studies have investigated the association between diet quality and sleep, but these associations have not been confirmed in meta‐analyses. A meta‐analysis was performed to analyze whether there was an association between sleep disorders and HEI. Methods A comprehensive search of several databases, including PubMed, Cochrane, Medline, Web of Science, and EMBASE, was conducted to identify relevant available studies reporting the relationship between sleep quality, abnormal sleep time, and HEI. Study results were meta‐analyzed using the odds ratios (ORs) and their 95% confidence intervals (95% CIs). Results A total of five observational studies were involved in the final analysis. Meta‐analysis showed that higher HEI scores are associated with lower risk of poor sleep quality (OR = 0.860; 95% CI, 0.743–0.997; p = 0.045). The higher the HEI scores, the lower the risk of abnormal sleep time (OR = 0.296; 95% CI, 0.088–0.987; p = 0.048). Conclusion The higher HEI score is associated with good sleep quality and a reduced risk of abnormal sleep time.